Volume 2: Combustion, Fuels and Emissions, Parts a and B 2011
DOI: 10.1115/gt2011-45295
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multiple-Injection-Burner Configurations on Combustion Characteristics for Dry Low-NOx Combustion of Hydrogen-Rich Fuels

Abstract: The successful combination of coal-based integrated gasification combined cycle (IGCC) technology with carbon dioxide (CO2) capture and storage (CCS) requires gas turbines that can achieve dry low-NOx combustion of hydrogen-rich syngas with a wide range of hydrogen concentrations for lower emissions and higher plant efficiency. The authors have been developing a “multiple-injection burner” to achieve dry low-NOx combustion of such hydrogen-rich fuels. The purpose of this paper is to experimentally investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…A similar concept but with micro-premixing channels has been called 'Multi-Tube Mixer' by GE [33]. The micro-premixed 'multiple-injection burner' was researched by MHPS and Hitachi [34].…”
Section: Stationary Gas Turbine Combustionmentioning
confidence: 99%
“…A similar concept but with micro-premixing channels has been called 'Multi-Tube Mixer' by GE [33]. The micro-premixed 'multiple-injection burner' was researched by MHPS and Hitachi [34].…”
Section: Stationary Gas Turbine Combustionmentioning
confidence: 99%
“…Operability similar to LDI can be attained in MM burners with careful design. LDI has been used in H 2 combustion to eliminate the risks associated with flashback. , The used configurations incorporated swirl-based mixing in small cups with radial and axial inflow, co-flow mixing, and jet-like cross-flow mixing …”
Section: Existing Burner Technologies In Lpm Gas Turbinesmentioning
confidence: 99%
“…The convex burner was equipped with a convex perforated plate, of which the center projected into the combustion chamber and the surface was inclined. The combustion test showed that the convex burner was effective in suppressing the combustion oscillation and it expanded the operating range of stable low NOx combustion [23].…”
Section: Combustor Development 41 Development Approachmentioning
confidence: 99%